Some Notes on the Obsolescence of Accounting Textbooks. - Most, Kenneth S. (The Accounting Review, 1974)
This article discusses some problems which arise at an early stage in accounting instruction as a result of textbook obsolescence. Textbooks, invariably postulate a set for basic assumptions or contentions or principles of accounting; it is clear to the instructor or practitioner that these relate to published financial statements. It is certain that students acquire an unnecessarily restrictive view of accounting by mistakenly believing from the start that these propositions apply throughout the spectrum of accounting possibilities.